Local citizen survey 1991 - Göteborg survey - Johansson, Folke; Westerståhl, Jörgen; Strömberg, Lars (University of Gothenburg, 1992)
This survey forms part of the research program 'Demokrati i förändring'. The survey was carried out immediately after the local elections in 1991. Areas covered: Opinion on how well the local authority service works and on achievments needed in different fields; Activities of the political parties; Attempts on influencing political decisions in another way than through voting; Political commitment and opinion on the recruitment of politicians; Membership of organizations and associations; Confidence in a number of institutions; Difference in treatment of men and women; Relation to other countries and international organizations; Medical care and the county council activities; The quality of the information about political issues and how to get information; Opinion on the political parties and vote in the election to the parliament, county council and local government respectively; and a number of socio-economic background variables. Furthermore there is a number of questions only put to individuals living in the municipalities of Grästorp, Kävlinge, Lidköping and Luleå. In Göteborg the questionnaire also included questions about the district neighbourhood committees.

En medborgarundersökning i 28 svenska kommuner i anslutning till de kommunala valen 1991. Frågeområden som togs upp: Hur fungerar den offentliga servicen och hur stora insatser bör göras på olika områden; De politiska partiernas aktiviteter i olika sammanhang; Försök att påverka politiska beslut på andra sätt än genom att rösta; Politiskt engagemang och hur man ser på rekryteringen av politiker; Medlemskap i organisationer och föreningar; Förtroende för olika institutioner och behandlingen av män och kvinnor; Hur olika verksamheter fungerar och hur de bör fungera; Relationer till andra länder och till internationella organisationer; Sjukvård och landstingets verksamhet; Hur bra informationen är om olika politiska frågor och på vilket sätt man inhämtar information; Syn på de politiska partierna och röstning i valen till kommunfullmäktige, landsting och riksdagen; Bakgrundsfrågor. En serie frågor riktade sig enbart till de som var bosatta i Grästorp, Kävlinge, Lidköping och Luleå. Den undersökning som gjordes i Göteborg innehöll även frågor om stadsdelsnämnder.
Kommunmedborgarundersökningen 1991 - Göteborgsundersökning
Keywords: local government elections; kommunalval; trust; förtroende; child care; barnomsorg; voting; röstning; parliamentary elections; riksdagsval; european union; europeiska unionen; political interest; politiskt intresse; membership; medlemskap; information sources; informationskällor; community action; samhällsengagemang; public services; offentlig service; privatization; privatisering; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; political parties; politiska partier; parliamentary candidates; riksdagskandidater; citizen participation; medborgardeltagande; state health services; statlig hälso- och sjukvård; political party policies; politiska partiers politik; lobbying; politisk påverkan; Information society; Informationssamhället; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Specific social services: use and availability; Specifika sociala tjänster: användning och tillgänglighet; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap